Financial Inclusion in Indonesia: An Analysis of Determinants of Bank Account Ownership and Credit Access at Individual and Regional Levels - Sahputri, Rindi Ardika Melsalasa; Sujarwoto, Sujarwoto; Sihombing, Septiana; Njoman, Muhamad Galy (Economics and Finance in Indonesia, 2024)
Financial inclusion is widely recognized as a key driver of economic prosperity, yet many countries face considerable challenges in achieving it. This study empirically explores financial inclusion in Indonesia, focusing on bank account ownership and credit access, with the primary objective of identifying their determinants through a comparison of individual- and regional-level factors. Individual-level factors cover sociodemographic characteristics, poverty, and income inequality, while regional-level factors include regional economic development and financial infrastructure. Data were sourced from the National Socio-Economic Survey (SUSENAS) and the Village Potential Survey (PODES), consisting of 804,703 samples across 514 districts. A multilevel regression approach, using Generalized Linear Latent and Mixed Models (GLLAMM), was employed to estimate the contributions of these factors to bank account ownership and credit access. Results reveal gaps in credit access and bank account ownership across regions, with individual-level factors emerging as prominent determinants of financial inclusion compared to district-level factors.